Using Kahoot! In Distance Learning To Increase Engineering Students English Skill - Fitri Senny Hapsari; Nurul Frijuniarsi; Natalia Tri Astuti (Journal of Development Research, 2021)
Since April 2020 The Ministry of Education stated the “Learning from Home” policy, that’s why The research was conducted during the COVID-19 pandemic in the academic year of 2020-2019 starting in April 2021. Where learning is learning process have been held virtually with the support of internet and some communication and computer-based device. As a matter of fact, distance learning is not as simple as it should be. So the purpose of this research is to improve grammar skills through interactive learning media so that it is interesting and does not make students bored while following the distance learning. Therefore, the authors conducted research by knowing the use of learning media based on Kahoot as an effort to improve students' English grammar skills. The research method applied is the Classroom Action Research Method which goes through 2 cycles with the final results showing that the use of kahoot as an alternative learning media is very effective in growing up the enthusiasm of students to attend lectures so that it has an impact on improving students' English grammar skills with the finding of the average score of students with The number of 70 in the first cycle and 80 as the average value in the second cycle, these results significantly increased from the average score of 60 before the implementation of kahoot as learning media.